O insuportável ruído dos crimes de honra na Palestina. Maria’s Grotto no coração dilacerado da nação - Teresa Cunha (e-cadernos ces)
Maria’s Grotto is a 2007 film on crimes of honour in contemporary Palestine by Palestinian director Buthina Khoury. The three film narratives converge and repel each other on and off, so that, in the process of rapprochement and mutual exasperation, the film plot comes together in the images, voices and silences of the documentary. One listens to and watches three narratives that evolve throughout time and take shape through the spaces and times where the four stories of those four Palestinian women are told. In this essay I try not only to listen to the voices, but also to see the faces, places, and gestures with which these women interrupt the unbearable loudness of women murdered in Palestine as a result of being accused of dishonouring their families. My main goal is not to theorize about this movie, but rather to reflect upon it based on a feminist post-colonial approach.